ASSESSMENT TECHNIQUES FOR YOUNG LEARNERS :A CASE STUDY AT ENGLISH CLASSROOMS OF SIX GRADERS IN THREE ELEMENTARY SCHOOLS IN BANDUNG - Chaerun Nissa, - (2010)
This research paper is entitled "Assessment Techniques for Young Learners: A Case Study at English Classrooms of Six Graders in Three Elementary Schools in Bandung". It aims to identify assessment techniques employed by English teachers in those schools and to know some reasons why they choose the assessment techniques. Data were collected from two research instruments namely interviews and classroom observations. To analyse the data, The Principle of Assessing Children's Language learning by Cameron (2001) was applied. The result shows that english teachers mostly use written tests for practicality purpose, instead of using oral tests, observations and take-home tasks. They use oral tests to know students' speaking ability. While observations done to assess non-linguistics aspects of the students. Take-home tasks is intended to give more chance for the students to use English outside their school. To apply suitable assessments, teachers are recommended to choose each of them carefully by considering the